Strategic Integration of Internal and External Environments through Innovation for Enhancing Organizational Performance - Fandi Achmad; Zulmi Ramdani; Iwan Inrawan Wiratmadja (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
The complexity of the challenges faced by modern industries stems not only from internal factors such as organizational structure and corporate culture, but also from external factors such as the intensity of market competition and the dynamics of changing consumer trends. Both of these aspects require in-depth strategic attention, particularly in the context of the highly dynamic tourism industry. Therefore, this study aims to understand how the interaction between the internal and external environments affects the performance of tourism organizations, with a focus on innovation as a key driver in addressing the complexities of the tourism industry environment. This research method uses a quantitative Partial Least Square Structural Equation Model (PLS-SEM)approach, which models the relationships between variables and identifies key factors that influence performance outcomes. Data collection was carried out through questionnaires involving respondents from various levels in SMEs around tourist areas. The results of the study reveal a significant relationship between the internal and external environments and innovation, as well as their impact on the performance of tourism organizations. Practical implications for stakeholders include developing more targeted innovation strategies, increasing internal capacity for innovation, and responding more effectively to changes in the external environment.